2008
DOI: 10.1002/bit.21839
|View full text |Cite
|
Sign up to set email alerts
|

Identification of novel small molecule enhancers of protein production by cultured mammalian cells

Abstract: Small molecule additives to cell culture media (e.g., sodium butyrate) that are capable of enhancing the expression of recombinant proteins have significant utility in the production and manufacture of therapeutic polypeptides. To identify novel small molecule enhancers (SMEs) of recombinant protein expression in Chinese Hamster Ovary (CHO) cells, we screened two separate small molecule libraries for compounds capable of enhancing the expression of either a fluorescent reporter protein or a monoclonal antibody… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
31
0
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(34 citation statements)
references
References 29 publications
0
31
0
1
Order By: Relevance
“…Histone deacetylase inhibitors (iHDACs) such as VPA, trichostatin A, and sodium butyrate, when applied to mammalian cells in vivo or in vitro, can prevent the transcriptional silencing of genes. Several iHDACs have been shown to enhance recombinant protein yields in transiently and stably transfected mammalian cells (Allen et al, 2008;Backliwal et al, 2008b;Choi et al, 2005;Davie, 2003;Gorman et al, 1983). Although it has been reported that transiently transfected plasmid DNA becomes complexed with histones that undergo post-translational modifications (Riu et al, 2007), it is not clear if the iHDACs mentioned above enhance TGE yields directly through effects on the histones associated with plasmid DNA or indirectly through effects on cellular gene expression.…”
Section: Introductionmentioning
confidence: 96%
“…Histone deacetylase inhibitors (iHDACs) such as VPA, trichostatin A, and sodium butyrate, when applied to mammalian cells in vivo or in vitro, can prevent the transcriptional silencing of genes. Several iHDACs have been shown to enhance recombinant protein yields in transiently and stably transfected mammalian cells (Allen et al, 2008;Backliwal et al, 2008b;Choi et al, 2005;Davie, 2003;Gorman et al, 1983). Although it has been reported that transiently transfected plasmid DNA becomes complexed with histones that undergo post-translational modifications (Riu et al, 2007), it is not clear if the iHDACs mentioned above enhance TGE yields directly through effects on the histones associated with plasmid DNA or indirectly through effects on cellular gene expression.…”
Section: Introductionmentioning
confidence: 96%
“…Nevertheless, it is still challenging to find out the main mechanisms of enhanced gene transcription due to the complexity of both YE components and transcription process itself. Previous studies showed that the addition of small molecules such as hydroxamic acids (Allen et al 2008;Jiang and Sharfstein 2008) and alkanoic acids (Liu et al 2001;Yang et al 2014) could enhance the transcription of heterologous gene by preventing the deacetylation of specific histone lysine residues. These findings encouraged us to speculate that some organic acids in YE should have the similar function.…”
Section: Discussionmentioning
confidence: 99%
“…A wide variety of molecules have been used to accomplish this, including quinoline thioethers [12], dimethyl sulfoxide [3,7,[13][14][15], and aurintricarboxylic acid [7]. Additionally, broad classes of small molecules including aromatic carboxylic acids, hydroxamic acids, and acetamides have been studied [16].…”
Section: Discussionmentioning
confidence: 99%